Aero‐servo‐elastic co‐optimization of large wind turbine blades with distributed aerodynamic control devices - Nikhar J. Abbas; Pietro Bortolotti; Christopher Kelley; Joshua Paquette; Lucy Pao; Nick Johnson (Wind Energy, 2023)
Abstract This work introduces automated wind turbine optimization techniques based on full aero‐servo‐elastic models and investigates the potential of trailing edge flaps to reduce the levelized cost of energy (LCOE) of wind turbines. The Wind Energy with Integrated Servo‐control (WEIS) framework is improved to conduct the presented research. Novel methods for the generic implementation and tuning of trailing edge flap devices and their controller are also introduced. Primary flap and controller parameters are optimized to demonstrate potential maximum blade tip deflection reductions of 21%. Concurrent design optimization (i.e., co‐design) of a novel segmented wind turbine blade with trailing edge flaps and its controller is then conducted to demonstrate blade cost savings of 5%. Additionally, rotor diameter co‐design optimization is demonstrated to reduce the LCOE by 1.3% without significant load increases to the tower. These results demonstrate the efficacy of control co‐design optimization using trailing edge flaps, and the entirety of this work provides a foundation for numerous control co‐design‐oriented studies for distributed aerodynamic control devices.